TYPOLOGY OF FEMALE IMAGES IN JANE AUSTEN'S NOVEL «SENSE AND SENSIBILITY”: THE PROBLEM OF TRANSLATING KEY CONCEPTS - Ilkiv, A. V.; Tsurkan, M. V.; Krynytska, O. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The purpose of the article is to investigate the typology of female images in the British literature of the Victorian era using the example of the novel by the British writer Jane Austen, to show the ways of artistic embodiment of gender roles in the plot of the text. Methodological principles of research. The article used general scientific and special literary methods. Of the general scientific ones, the structural-systemic method and the classification method were applied, which made it possible to consider the research object as a single whole. Among the special literary methods, the comparative-typological method was used (for the typology of female images in the novel); comparative-historical and contextual (to study the traditions of feminist criticism and the historical-cultural discourse of British literature); descriptive and structuralist (when determining problem-thematic gender dominants). The results of the study showed that the image of the "new woman" in Jane Austen's novel "Sense and Sensibility" was innovative in many ways. This image can be considered partly autobiographical, because in it the reader can recognize the character traits of the writer herself, endowed with a lively mind, common sense and analytical thinking. It was important for Jane Austen to show the evolution of women during the struggle for women's rights and the emergence of the idea of women's emancipation. That is why her new ideal becomes a thinking woman, a woman who is able to control her emotions and feelings, a woman who is capable of deep feelings, but one who does not follow the first call of the heart, but relies on rational thinking. The novelty of the article lies in the fact that the specifics of the implementation of gender ideology in the artistic text became the subject of a separate study, the role of female self-education as the main characteristic of the image of the "new woman" in the novel "Sense and Sensibility" was determined; ways of harmonizing binary patriarchal-matriarchal relations at the plot and image levels of the novel are outlined. The practical significance is that the main provisions and conclusions of the article can be used for analytical investigations of British literature of the Victorian period, in particular, the study of the role of Jane Austen's work in the process of formation of the feminist discourse of British literature.